Asymmetric Races of Research and Development - Flavio Delbono; Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
In this paper we study a one-shot game of R&D between two price-setting firms that are asymmetrically placed as they produce at different cost levels. First we prove the existence and the properties of a noncooperative equilibrium. Then, we show that the higher (lower) the discount rate, the lower (higher) the probability of innovating of the current leader. In a specialised version of the model we establish the effect of the productivity of R&D espenditure, initial cost gap, and market size on the expected identity of the winner of the patent race.
Keywords: 330